Cu-Mediated Aminoquinoline-Directed Radiofluorination of Aromatic C–H Bonds with K(18)F - Lee, So Jeong (Angew Chem Int Ed Engl, 2019)
This communication describes a Cu-mediated ortho-C–H radiofluorination of aromatic carboxylic acids that are protected as 8-aminoquinoline benzamides. The method uses K(18)F and is compatible with a wide range of functional groups. The reaction is showcased in the high specific activity automated synthesis of the RARβ2 agonist [(18)F]AC261066.